2020
DOI: 10.1016/j.ijheh.2020.113621
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan wastewater analysis for COVID-19 epidemiological surveillance

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(139 citation statements)
references
References 28 publications
4
131
0
4
Order By: Relevance
“…The improved utilization of established methods and the changing analytical techniques began incorporating nanoor micro-sized magnetic beads (MBs) [39]. Randazzo et al [6] indicated that the presence of surface functional groups creates a speedy response to an applied magnetic field, uniform and high magnetite content, homogenous size distribution and colloidal stability of magnetic nanoparticles which are some of the specific properties of MBs in the analytical applications. The magnetic behavior associated with magnetic nanoparticles, mostly of ferromagnetic materials, enhances simple isolation of analytes from complex matrices such as environmental and biological samples [39].…”
Section: Magnetic Nanotechnologymentioning
confidence: 99%
See 4 more Smart Citations
“…The improved utilization of established methods and the changing analytical techniques began incorporating nanoor micro-sized magnetic beads (MBs) [39]. Randazzo et al [6] indicated that the presence of surface functional groups creates a speedy response to an applied magnetic field, uniform and high magnetite content, homogenous size distribution and colloidal stability of magnetic nanoparticles which are some of the specific properties of MBs in the analytical applications. The magnetic behavior associated with magnetic nanoparticles, mostly of ferromagnetic materials, enhances simple isolation of analytes from complex matrices such as environmental and biological samples [39].…”
Section: Magnetic Nanotechnologymentioning
confidence: 99%
“…Recently, applications of magnetic separation have been introduced in biotechnology for analytical applications, separation of cells, sewage treatment, protein digestion and purifications [6,9,34,39]. Furthermore, integrating MBs with aptamers opens up additional opportunities in various applications including disease diagnosis using biosensors, cell imaging and labelling and magnetic resonance imaging, disease therapy, water purification, wastewater treatment, sewage treatment, and sample preparation [34,39].…”
Section: Magnetic Nanotechnologymentioning
confidence: 99%
See 3 more Smart Citations